Morality of Online Gambling Students and Online Loan Customers in Banyumas - Wati, Ratna Kartika; Faridli, Efi Miftah (Universitas PGRI Kanjuruhan Malang, 2024)
The aim of this research is to analyze and describe students' involvement in online gambling games and online loans and their morality in terms of Piaget's theory of moral development. The research method is a qualitative approach. Data sources were obtained through interviews. The data analysis technique uses qualitative analysis techniques from Cresswell.The results of this research are (1) The process of reconstructing students in online gambling games and online loans is through a trial and error stage due to the invitation of friends, over time it becomes an addiction and a necessity, (2) the students who were informants in this research were in the moral education level category according to Jean Piaget at level 3, namely basically egocentricity has been reduced, and the application of norms has become an activity. social. (3) The results of this research are certainly a critical study, that the setting of age ranges in Jean Piaget's theory of moral development needs to be re-examined, because a student who has Ages above the age limit set by Jean Piaget are still experiencing a developmental.